Reputation: 29
module Parser where
import Control.Monad (MonadPlus, mplus, mzero)
import Tagger (Tag, Token)
newtype Parser a = Parser ([(Token, Tag)] -> [(a, [(Token, Tag)])])
parse :: Parser a -> [(Token, Tag)] -> [(a, [(Token, Tag)])]
parse (Parser p) = p
instance Functor Parser where
fmap f p = do
result <- p
return (f result)
instance Monad Parser where
return a = Parser (\cs -> [(a,cs)])
p >>= f = Parser (\cs -> concat [parse (f a) cs' | (a,cs') <- parse p cs])
instance MonadPlus Parser where
p `mplus` q = Parser (\cs -> parse p cs ++ parse q cs)
mzero = Parser (const [])
{-
This is my code for my parser. Apparently I've done it "the old way" and cannot really get it to work the new way. Can you tell me which things I need to fix in order to make it work? I read this article (https://wiki.haskell.org/Functor-Applicative-Monad_Proposal) and tried to change my code but I think I'm doing something wrong here.
The compiling errors I get:
Parser.hs:56:10:
No instance for (Applicative Parser)
arising from the superclasses of an instance declaration
In the instance declaration for ‘Monad Parser’
Parser.hs:60:10:
No instance for (GHC.Base.Alternative Parser)
arising from the superclasses of an instance declaration
In the instance declaration for ‘MonadPlus Parser’
EDIT //
The code right now:
module Parser where
import Control.Applicative
import Control.Monad (mplus, mzero, liftM, ap)
import Tagger (Tag, Token)
-- type Token = String
-- type Tag = String
newtype Parser a = Parser ([(Token, Tag)] -> [(a, [(Token, Tag)])])
parse :: Parser a -> [(Token, Tag)] -> [(a, [(Token, Tag)])]
parse (Parser p) = p
instance Functor Parser where
fmap = liftM
instance Applicative Parser where
pure a = Parser (\cs -> [(a,cs)])
(<*>) = ap
instance Monad Parser where
p >>= f = Parser (\cs -> concat [parse (f a) cs' | (a,cs') <- parse p cs])
instance MonadPlus Parser where --64
p `mplus` q = Parser (\cs -> parse p cs ++ parse q cs)
mzero = Parser (const [])
instance Alternative Parser where
(<|>) = mplus
empty = mzero
(+++) :: Parser a -> Parser a -> Parser a
p +++ q = Parser (\cs -> case parse (p `mplus` q) cs of
[] -> []
(x:_) -> [x])
Error:
Parser.hs:64:10:
Not in scope: type constructor or class ‘MonadPlus’
Upvotes: 3
Views: 950
Reputation: 3080
You may follow the migration guide. It's simple and straightforward: move the definition of return
to pure
, add the boilerplate definition of <*>
and remove return
from the monad instance:
instance Functor Parser where
fmap = liftM
instance Applicative Parser where
pure a = Parser (\cs -> [(a,cs)])
(<*>) = ap
instance Monad Parser where
p >>= f = Parser (\cs -> concat [parse (f a) cs' | (a,cs') <- parse p cs])
For Alternative
it's boilerplate and nothing else:
instance Alternative Parser where
(<|>) = mplus
empty = mzero
The working code as a whole:
module Parser where
import Control.Monad
import Tagger (Tag, Token)
import Control.Applicative
newtype Parser a = Parser ([(Token, Tag)] -> [(a, [(Token, Tag)])])
parse :: Parser a -> [(Token, Tag)] -> [(a, [(Token, Tag)])]
parse (Parser p) = p
instance Functor Parser where
fmap = liftM
instance Applicative Parser where
pure a = Parser (\cs -> [(a,cs)])
(<*>) = ap
instance Monad Parser where
p >>= f = Parser (\cs -> concat [parse (f a) cs' | (a,cs') <- parse p cs])
instance MonadPlus Parser where
p `mplus` q = Parser (\cs -> parse p cs ++ parse q cs)
mzero = Parser (const [])
instance Alternative Parser where
(<|>) = mplus
empty = mzero
Upvotes: 3